Copy number variation in female infertility and candidate gene screening for common infertility-related diseases - Kozhabek, Zh.; Pang, M.; Zhao, Q. Zh.; Yi, J.Y.; Huang, W.D. (Fundamental and Experimental Biology, 2021)
To investigate the correlation between the gene copy number variation and female infertility we collected 3962 female infertility samples and analyzed copy number variation (CNV) using high-throughput sequencing technologies. In this study 269 CNVs were found in 246 samples, 17 of which were new CNVs. The occurrence of CNVs was mostly found in X chromosome, and some candidate genes related to female infertility were screened. We also found some high frequency CNVs, which contain important functional genes. This study filled the blank of CNV research on femaleinfertility and discovered the characteristics of CNV (CNV preference, recurrent CNV), which provided genetic reference for female infertility.